Multimedia constructivism instrument: Validity and reliability analysis - Zaharah Che Isa; Nurulwahida Azid (Institute of Advanced Engineering and Science, 2022)
This study aimed to investigate the use of the translated version of constructivism multimedia instrument through validity and reliability tests. The instrument contained five constructs of which each construct contained five items which made 25 items in total. The translation process has been implemented through the back-translation by researchers and expert translators. The validation process was performed by nine panel experts who are lecturers in the field of Language and curriculum. The results of validity analysis through intraclass correlation coefficient (ICC) found that the reliability value between evaluators was .957 based on 95% confidence interval between .904 to .989 (F (8,192)=23.469, p<.05). Meanwhile, the process of obtaining the reliability value was conducted on 70 students and obtained a high overall reliability value of the instrument which was .853. In addition, the reliability values for each construct of the multimedia constructivism learning instrument were .753 (negotiation), .780 (inquiry learning), .691 (reflective thinking), .683 (authenticity) and .803 (complexity). Overall, the high values of validity and reliability of the instrument proved that this translation study has been successfully implemented.